Role of N-glycosylation in structural stability and binding specificity of IL-1ra antagonist to it receptor: an efficient approach to engineer therapeutic proteins - Anith Kumar Rajendran; Kalimuthu Karuppanan; Senthilkumar Palanisamy (Discover Applied Sciences)
Abstract Interleukin-1 receptor antagonist (IL-1ra) is a vital anti-inflammatory molecule, acting as a decoy protein that competitively binds to Interleukin-1 receptors (IL-1RI and IL-1RII). The deregulation of IL-1 activity has been linked to autoimmune disorders, impaired wound healing, and the occurrence of cytokine storms in the context of infections. At present, E.coli expressed IL-1ra isoform was used as a therapeutic drug for the treatment of IL-1 mediated inflammatory diseases; however, daily dosing raises concerns about allergens and infection. Notably, the drug lacks glycosylation, an important post-translational modification for protein stability and pharmacodynamics. The present study utilizes computational molecular dynamics simulations to investigate the influence of glycosylation on the stability and binding efficacy of IL-1ra. To study the impact, we introduced mammalian bi-antennary hybrid glycan with terminal sialic acid/ N-Acetylneuraminic acid (Neu5Ac) added to the respective Asparagine (Asn) residue of 3D modeled IL-1ra structure. The molecular dynamics simulations demonstrated that glycosylated IL-1ra increased the structural stability and exhibited a sustained level of binding stability with 24 hydrogen bonds and 8 salt bridges in comparison to non-glycosylated IL-1ra protein with 20 hydrogen bonds and 6 salt bridges as the result of post simulation. This finding underscores the possibility of glycosylation as it means to augment the effectiveness of therapeutic medications that specifically target immune regulation. These understandings help to translate the concept to the complete expression of proteins. Our study addressed the mechanism of how the N-glycan regulates cytokine, which will provide insight into the design of novel anti-inflammatory drugs and specifically glycan play a role in RA.